2020
DOI: 10.3390/molecules25194469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biogenic Gold Nanoparticles from Terminalia mantaly Extracts and the Evaluation of Their In Vitro Cytotoxic Effects in Cancer Cells

Abstract: Scientists have demonstrated the potential of plant materials as ‘green’ reducing and stabilizing agents for the synthesis of gold nanoparticles (AuNPs) and opened new ecofriendly horizons to develop effective and less harmful treatment strategies. The current study demonstrated the use of Terminalia mantaly (TM) extracts to synthesize AuNPs with enhanced cytotoxic effects. The TM-AuNPs were synthesized at 25 and 70 °C using water (WTM) and methanolic (MTM) extracts of the leaf, root and stem/bark parts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…So, this assay has demonstrated the selective character of UCA01, showing an antiproliferative effect on the Caco-2 and HepG2 tumor lines, while it showed no effect on the EA.hy926 nontumor line ( Figure 3 ). Differences observed between Caco-2 and HepG2 in terms of effective antiproliferative concentrations are in line with recent previous reports showing differences in values obtained in these cell lines [ 67 , 68 , 69 ]. The relevance of discovering an antiproliferative protein in a microalga demonstrates the potential that microalgae have in the search for new compounds that could help humans and, of course, the potential of “Applied Proteomics” to identify them.…”
Section: Discussionsupporting
confidence: 90%
“…So, this assay has demonstrated the selective character of UCA01, showing an antiproliferative effect on the Caco-2 and HepG2 tumor lines, while it showed no effect on the EA.hy926 nontumor line ( Figure 3 ). Differences observed between Caco-2 and HepG2 in terms of effective antiproliferative concentrations are in line with recent previous reports showing differences in values obtained in these cell lines [ 67 , 68 , 69 ]. The relevance of discovering an antiproliferative protein in a microalga demonstrates the potential that microalgae have in the search for new compounds that could help humans and, of course, the potential of “Applied Proteomics” to identify them.…”
Section: Discussionsupporting
confidence: 90%
“…Munawer et al also evaluated anticancer potential of AuNPs developed using the aqueous extract of Commiphora wightii and observed an IC 50 of 66.11 μg/mL against the breast cancer cell line [ 31 ]. Several studies have described the in vitro cytotoxic effects of biogenic AuNPs on several cancer cell lines such as MCF 7, Caco-2, HePG2, and KMST-6 [ 32 ]. Similarly, other studies have observed that 100 μg/mL of biogenic AuNPs synthesized using Nothaphodytes foetida was required to inhibit 90% growth of HeLa, MCF-7, and HCT-15 cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…AuNPs-conjugates were reported to significantly enhanced the selectivity as well as the sensitivity of therapeutic peptides on pancreatic (Panc-1) and colon (Caco-2) cancer cells [ 53 , 54 ]. According to previous and recent studies, biosynthesized AuNPs have achieved significant targeting and selectivity against a variety of cancer cells without any additional molecules [ 19 ]. A study by Majoumouo et al [ 19 ] demonstrated that the AuNPs synthesized using Terminalia mantaly exhibited enhanced cytotoxicity and selectivity on Caco-2, epithelial breast (MCF-7), and liver (HepG2) cancer cells.…”
Section: Mnps and Their Applicationmentioning
confidence: 99%
“…According to previous and recent studies, biosynthesized AuNPs have achieved significant targeting and selectivity against a variety of cancer cells without any additional molecules [ 19 ]. A study by Majoumouo et al [ 19 ] demonstrated that the AuNPs synthesized using Terminalia mantaly exhibited enhanced cytotoxicity and selectivity on Caco-2, epithelial breast (MCF-7), and liver (HepG2) cancer cells. Another study by Anadozie and co-workers [ 19 ] revealed that AuNPs synthesized from water extract of Xylopia aethiopica showed excellent anticancer activity on MCF-7 and Caco-2 cells.…”
Section: Mnps and Their Applicationmentioning
confidence: 99%
See 1 more Smart Citation